Analysis of Rainfall as an Agroclimatological Element on Production and Determining the Planting Season of Shallots (Allium Cepa L.) in South Tapanuli Regency - Harahap, Imelda Sari; Soleh, Hery (PT FORMOSA CENDEKIA GLOBAL, 2024)
The amount of rain that falls affects the availability of water for planting. For planting scheduling purposes, farmers still use conventional techniques. In our opinion, this decision is not the best. This research aims to determine the relationship between rainfall and the suitability of sweet potato plants by analyzing the impact of rainfall in South Tapanuli Regency on shallot production using rainfall data. Literature review and survey approach were the research methods used. This research uses a survey methodology using descriptive and correlational methodology to ascertain the relationship between rainfall and precipitation. The weakness of this positive influence is shown by the results of regression analysis and correlation of rainfall variables with the magnitude of productivity variables from research conducted a decade earlier. This information was conveyed by the South Tapanuli Regency Central Statistics Agency.